PRODUCT, PROCESS, MARKETING AND ORGANIZATIONAL INNOVATION IN INDUSTRIES OF THE FLAT KNITTING SECTOR (INMR - Innovation & Management Review, 2018)
Innovation practice contributes to economic development by fostering the development of new markets and the improvement of existing markets. This study aimed to identify the innovations in the flat knitting industry that occurred between 2008 and 2011. This applied nature study considers both qualitative and quantitative approaches with exploratory and descriptive purposes as its research method. A survey addressed to managers of 23 flat knitting industries was conducted. Data analysis was carried out in two stages: in the qualitative stage, content analysis of the interview was performed, while in the quantitative stage, a descriptive quantitative analysis through correlation statistics was used, in order to identify the level of relationship between the variables of the theoretical construct. The results of the qualitative stage showed that the flat knitting industry invests in innovation compatible with the market demands and fashion trends. The quantitative results identified relationships among the variables named annual turnover, number of employees and amount invested in marketing innovation. In addition, correlations were also observed among the variables skilled workforce and amount invested both in product and organizational innovation, and a relationship was identified between amount invested in product innovation and amount invested in marketing innovation.